Crime and its socio-macroeconomics determinants: a panel-error-correction cointegration analysis - Abdul Hamid, Baharom; Habibullah, Muzafar Shah; Mohd Noor, Zaleha (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study investigates the relationship between crime and socio and macro economic variables such as income, unemployment, inflation, interest rate, and also the political violence, both domestic and regional. The main motivation of the study is to have a better understanding of crime as well as finding and suggesting alternative ways of approaching crime. We analyzed 21 countries, with data spanning from 1960 to 2001.We adopted the model and framework introduced by Viren (2001) based on Becker (1968), Block and Heineke (1975). However, we slightly modified by rephrasing it in order not to only capture the long run relationship but also the short run adjustment. We employed the panelerror- correction based cointegration (Persyn and Westerlund (2008)) to analyze and estimate the model. A number of important findings are extracted from the analysis in accordance to the objectives of this study. Firstly, we discover a negative long run relationship between income and crime; positive long run relationship between inflation and crime; unemployment and crime; as well as lending rate and crime. As for the political violence variable, domestic political violence seems to be negatively related; on the contrary regional political violence is positively related. We believe this might be attributed to the spillover effect. All the signs are as anticipated and justified in this study; and are concurrent with most of the past literatures.